Ebola outbreak in rural West Africa: epidemiology, clinical features and outcomes. Issue 4 (3rd February 2015) - Dallatomasina, Silvia; Crestani, Rosa; Sylvester Squire, James; Declerk, Hilde; Caleo, Grazia Marta; Wolz, Anja; Stinson, Kathryn; Patten, Gabriela; Brechard, Raphael; Gbabai, Osman Bamba‐Moi; Spreicher, Armand; Van Herp, Michel; et al.
Abstract Objective To describe Ebola cases in the district Ebola management centre of in Kailahun, a remote rural district of Sierra Leone, in terms of geographic origin, patient and hospitalisation characteristics, treatment outcomes and time from symptom onset to admission. Methods Data of all Ebola cases from June 23rd to October 5th 2014 were reviewed. Ebola was confirmed by reverse‐transcriptase‐polymerase‐chain‐reaction assay. Results Of 489 confirmed cases (51% male, median age 28 years), 166 (34%) originated outside Kailahun district. Twenty‐eight (6%) were health workers: 2 doctors, 11 nurses, 2 laboratory technicians, 7 community health workers and 6 other cadres. More than 50% of patients had fever, headache, abdominal pain, diarrhoea/vomiting. An unusual feature was cough in 40%. Unexplained bleeding was reported in 5%. Outcomes for the 489 confirmed cases were 227 (47%) discharges, 259 (53%) deaths and 3 transfers. Case fatality in health workers (68%) was higher than other occupations (52%, P = 0.05). The median community infectivity time was 6.5 days for both general population and health workers (P = 0.4). Conclusions One in three admitted cases originated outside Kailahun district due to limited national access to Ebola management centres – complicating contact tracing, safe burial and disinfection measures. The comparatively high case fatality among health workers requires attention. The community infectivity time needs to be reduced to prevent continued transmission.